2017
DOI: 10.1177/2049463717695144
|View full text |Cite
|
Sign up to set email alerts
|

Schoolbags and back pain in children between 8 and 13 years: a national study

Abstract: Schoolbag weight in schoolchildren is a recurrent and contentious issue within the educational and health sphere. Excessive schoolbag weight can lead to back pain in children, which increases the risk of chronic back pain in adulthood. There is limited research regarding this among the Maltese paediatric population. A cross-sectional study was undertaken across all schools in Malta among students aged 8-13 years (inclusive). Data were collected using a questionnaire detailing schoolbag characteristics, self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 13 publications
2
57
2
3
Order By: Relevance
“…We observed no significant difference between the fifth-and sixth-grade students in relation to the schoolbag weight (≤10% or >10% of child body mass), and in both groups, about half of the students (48.5% in the fifth and 50% in the sixth grade) carried schoolbags weighing more than 10% of the body mass. Two other studies on the association between schoolbag weight and back pain in children showed that majority of students carried heavier schoolbags (>10% of the body mass) (27,28). Overall, these results indicate that schoolchildren are often required to carry schoolbags that are heavier than recommended.…”
Section: Discussionmentioning
confidence: 70%
“…We observed no significant difference between the fifth-and sixth-grade students in relation to the schoolbag weight (≤10% or >10% of child body mass), and in both groups, about half of the students (48.5% in the fifth and 50% in the sixth grade) carried schoolbags weighing more than 10% of the body mass. Two other studies on the association between schoolbag weight and back pain in children showed that majority of students carried heavier schoolbags (>10% of the body mass) (27,28). Overall, these results indicate that schoolchildren are often required to carry schoolbags that are heavier than recommended.…”
Section: Discussionmentioning
confidence: 70%
“…The notion that the excessive weight of schoolbags carried by school students can trigger LBP, makes clinical sense. Moreover, the cut-off point of > 10% of bodyweight defining an "excessive" weight to be carried, is indirectly supported by some evidence and has elicited consensus among clinicians, researchers and some professional associations American Chiropractic Association, 2018;American Occupational Therapy Association, 2017;American Physical Therapy Association, 2017;Devroey et al, 2007;Erne & Elfering, 2011;Grimmer & Williams, 2000;Mackie & Legg, 2008;Negrini et al, 1999;Sahli et al, 2013;Spiteri et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Establishing 10% of the bodyweight as the cut‐off point to consider the weight of the schoolbag as "excessive" may appear reasonable; it has some data supporting it and is equivalent to the threshold most commonly used for adults in the work‐related environment. This has led to most recommendations establishing that the "acceptable" weight for the schoolbag should be below this threshold (Alghadir et al, ; American Chiropractic Association, ; American Occupational Therapy Association, ; American Physical Therapy Association, ; Devroey et al, ; Erne & Elfering, ; Grimmer & Williams, ; Mackie & Legg, ; Negrini et al, ; Sahli et al, ; Spiteri et al, ). However, other cut‐off points have been proposed, as low as 5% or as high as 20% (Dockrell et al, ; Rateau, ).…”
Section: Discussionmentioning
confidence: 99%
“…Heavy school bags are one of the common factors that influence the incidence of musculoskeletal back pain and alteration of students' body posture. [20] The musculoskeletal system react properly to compensate for this stress and alteration. A limit weight of school bags not excess 15% of the body weight is one of the methods that decrease and prevent students' back pain.…”
Section: Discussionmentioning
confidence: 99%